DSGE Modeling at the Fund : Applications and Further Developments - Botman, Dennis (IMF Working Papers; Working Paper ;, 2007)
Researchers in policymaking institutions have expended significant effort to develop a new generation of macro models with more rigorous microfoundations. This paper provides a summary of the applications of two of these models. The Global Economy Model is a quarterly model that features a large assortment of nominal and real rigidities, which are necessary to create plausible short-run dynamics. However, because this model is based on a representative-agent paradigm, its Ricardian features make it unsuitable to study many fiscal policy issues. The Global Fiscal Model, which is an annual model that uses an overlappinggenerations structure, has been designed to analyze the longer-term consequences of alternative fiscal policies.